2017
DOI: 10.1177/0883073816687221
|View full text |Cite
|
Sign up to set email alerts
|

Vagus Nerve Stimulation in Intractable Epilepsy Associated With SCN1A Gene Abnormalities

Abstract: Mutations in the SCN1A gene cause a spectrum of epilepsy syndromes. There are 2 syndromes that are on the severe end of this spectrum. The classic severe form, Dravet syndrome, is an epileptic encephalopathy of childhood, causing cognitive decline as well as intractable seizures. Severe Myoclonic Epilepsy of Infancy-Borderline (SMEIB) is a term used to include cases with similar severities as those with Dravet syndrome, but lacking a single feature of classic severe myoclonic epilepsy of infancy. Vagus nerve s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 15 publications
(26 reference statements)
1
21
1
1
Order By: Relevance
“…In Lennox-Gastaut syndrome there were promising results 36 , with a 58% reduction in seizure frequency six months after implantation in a multicenter retrospective study of 50 patients 37 . SCN1A gene mutations might improve as well, as reported by Fulton et al 38 , who described a 75% rate of responders in 12 patients.…”
supporting
confidence: 52%
“…In Lennox-Gastaut syndrome there were promising results 36 , with a 58% reduction in seizure frequency six months after implantation in a multicenter retrospective study of 50 patients 37 . SCN1A gene mutations might improve as well, as reported by Fulton et al 38 , who described a 75% rate of responders in 12 patients.…”
supporting
confidence: 52%
“…Several studies showed the effectiveness of VNS in DS patients. 10,[29][30][31][32] However, how early in the disease process, VNS should be used is unclear. Dibué-Adjei et al performed a meta-analysis of 68 patients from 13 studies and found 52.9% of patients had more than 50% seizure reduction.…”
Section: Vagus Nerve Stimulation and Epilepsy Surgeriesmentioning
confidence: 99%
“…Fulton et al placed the vagus nerve stimulation for 12 patients with Dravet syndrome and assessed the seizure control after 6 months. Nine of them showed >50% reduction in generalized tonic-clonic seizures, and four of them showed the cognitive function improvement [87]. Neuroscientist screened the potential therapeutic agents and tested their effectiveness in vivo in the experimental setting.…”
Section: Treatment To Dravet Syndrome and Therapeutic Responsementioning
confidence: 99%